Permodelan Sistem Penjualan Mobil Bekas Menggunakan Web Engineering - Aliy Hafiz (Jurnal Ilmiah Informatika dan Ilmu Komputer (JIMA-ILKOM), 2023)
The main purpose of this study is to improve accessibility and convenience for potential buyers in finding, comparing, and buying used cars. This application should be designed with an intuitive and responsive user interface, so that users can make transactions easily using web engineering methods. Based on the results of the recapitulation of the 7 test criteria that have been carried out, the results of the number of answers from respondents are obtained which have a value of 100% in accordance with testing the functionality of the system using blackbox testing.